Efficacy of formulated feeds for juvenile green-back grey mullet Liza subviridis (Valenciennes) - Das, N G; Bhattacherjee, H; Khan, M I (Indian Journal of Fisheries, 2011)
The culture practice of green-back greymullet Liza subviridis is becoming popqlar.But no work has been conducted on feed formulationfor this species. This study showsthe effect of protein levels, protein sourcesand the natural planktonic food on thegrowth and survival of the species.